2008
DOI: 10.2989/ajas.2008.33.2.11.508
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an impoundment on nutrient dynamics in the Kihansi River, Tanzania

Abstract: The impact of the Kihansi Dam on electrical conductivity, pH, temperature and dissolved oxygen in the Kihansi River was assessed in 2005 after 85% of the original river flow had been diverted to the Lower Kihansi power plant. The results are compared with the data obtained in 1995 before the dam was constructed. Primary production and nitrogen and phosphorus concentrations from sites upstream and downstream of the dam as well as in the reservoir were compared. Phosphorus fractions were determined in the reserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
3

Year Published

2011
2011
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 24 publications
2
6
0
3
Order By: Relevance
“…The phosphate concentration and the turbidity of the water downstream from the dam were reduced by 67 and 83%, respectively, when compared to the upstream river water. This is in agreement with a study by Ideva et al (2008) in Tanzania, where these authors indicated that concentrations of nitrate and phosphate drastically decreased downstream compared to a site upstream from the dam. Alterations of the nutrient content in the downstream part may affect the primary production of the river system (Ideva et al 2008).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The phosphate concentration and the turbidity of the water downstream from the dam were reduced by 67 and 83%, respectively, when compared to the upstream river water. This is in agreement with a study by Ideva et al (2008) in Tanzania, where these authors indicated that concentrations of nitrate and phosphate drastically decreased downstream compared to a site upstream from the dam. Alterations of the nutrient content in the downstream part may affect the primary production of the river system (Ideva et al 2008).…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with a study by Ideva et al (2008) in Tanzania, where these authors indicated that concentrations of nitrate and phosphate drastically decreased downstream compared to a site upstream from the dam. Alterations of the nutrient content in the downstream part may affect the primary production of the river system (Ideva et al 2008). Electrical conductivity in the downstream part increased by 210% compared to the upstream site.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the world literature, the studies on the influence of storage reservoirs on the chemical composition (including nutrients concentrations) of rivers are focused both on single and numerous reservoirs localised in various regions, diversified in terms of physical and geographical characteristics [4,[6][7][8][9][10][11][12]. Mountain regions show high temporal and spatial diversification of all hydrological processes [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The project was closed on the Kihansi River in 2000 and diverted an estimated 85% of the river's flow. Studies have shown subsequent changes in water quality and community composition of wetland plants and amphibian species, most notably the endemic Kihansi Spray Toad (Nectophrynoides asperginis), whose only known habitat is the humid areas created by the spray of the original waterfall at the dam site [68,69]. Once the dam was closed and began operations, this spray habitat disappeared and an international captive breeding and reintroduction effort to save the toad from extinction was launched.…”
Section: River Alterations and Damsmentioning
confidence: 99%